Strategi Pembelajaran Computational Thinking Dalam Meningkatkan Capaian Belajar Kognitif Siswa Dalam Materi Akhlak Mata Pelajaran PAI Di Kelas X Multimedia SMK Plus Sukaraja - Amalia, Debby Rizki; Husna, Muhammad Lutfi Aripal; Abdullah, Deba Muslim (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This study is motivated by the observation that students in the 10th-grade Multimedia class at SMK Plus Sukaraja struggle with understanding the material, particularly in Islamic Religious Education (PAI) subjects. The students tend to focus more on vocational subjects that align with their major, leading to a cognitive decline in their learning process for PAI subjects. Additionally, teachers face difficulties managing students who are less focused and inattentive during lessons. To address these challenges, teachers have implemented strategies using a computational thinking approach in the learning process. This research focuses on the use of computational thinking strategies to enhance students' cognitive learning outcomes in the moral (akhlaq) component of the PAI curriculum. The objectives of this study are: (1) To assess the cognitive learning outcomes of students in the moral (akhlaq) component of the PAI subject for the 10th-grade Multimedia class at SMK Plus Sukaraja. (2) To explore the application of computational thinking strategies in the moral (akhlaq) component of the PAI subject at SMK Plus Sukaraja. (3) To evaluate the effectiveness of computational thinking strategies in improving students' cognitive learning outcomes in the moral (akhlaq) component of the PAI subject at SMK Plus Sukaraja. The research employs a field-based descriptive qualitative approach to answer these questions. Data analysis methods include data reduction, data presentation, and conclusion or verification. The findings of this research generally conclude that the application of computational thinking strategies can enhance students' cognitive learning outcomes. This is evidenced by increased student engagement in class, with more questions being asked, improved focus during lessons, and enhanced cognitive problem-solving skills as reflected in better evaluation results. Keywords: computational thinking, cognitive learning outcomes, Islamic religious education